Performance evaluation of lightweight normal and geopolymer foamed concrete using palm oil fuel ash as partial replacement of binder / Ahmed M. E. Alnahhal - Ahmed, M .E. Alnahhal (2020)
Carbon dioxide (CO2) emissions from Ordinary Portland Cement (OPC) have a detrimental effect on the environment and this had led many researchers to search for other alternatives in the form of sustainable cementitious materials. The depletion of natural resources and dumping the industrial by-products and waste materials are serious concern to our environment. This research focusses on the performance of using a palm oil industrial by-product, namely, palm oil fuel ash (POFA), as a partial replacement for OPC and fly ash (FA) in lightweight normal foamed concrete and lightweight geopolymer foamed concrete, respectively. Thus, using 10, 20, and 30% POFA as a replacement for OPC, and FA, foamed concrete was cast to achieve a target oven-dry density of 1300 kg/m3. In addition to the compressive and splitting tensile strengths, transport properties, such as water absorption, porosity, and sorptivity tests were carried out. The microstructural analyses were carried out using XRD, SEM, and EDS tests. Non-destructive tests – ultrasonic pulse velocity and electrical resistivity – were also performed. The results revealed that a replacement with 20% POFA produced comparable performance to other mixes and compressive strength of the lightweight geopolymer foamed concrete, with up to 30% POFA, was higher than the control, while conversely, for the POFA-based geopolymer mortar, the compressive strength was reduced with increasing POFA content. The highest compressive strengths recorded in the geopolymer foamed concrete with 20% POFA and in the control geopolymer mortar were 6.1 MPa, and 36.6 MPa, respectively. The geopolymer foamed concrete achieved 70% of its compressive strength within 3 days of the 28-day curing period. The results show that non-structural grade POFA based foamed concrete with a density reduction of about 36% could be produced with 10-30% of POFA as binder replacement. Although the UPV test results show the foamed concrete as doubtful quality, the use of industrial waste as a sustainable material could be envisaged in such non-structural concrete. In general, the transport properties were mostly dependent on the oven-dry density. The SEM results showed micro-cracks when OPC was replaced with 30% POFA. Further, a slight reduction in the intensity of the peaks of the crystalline phases was observed when a higher quantity of POFA was used as cement replacement, while conversely, for lightweight geopolymer foamed concrete the peaks intensity increased, and the SEM images showed the foam agent distract the matrix compared to the control mixes. The optimum level of POFA to provide the silica and alumina required to produce sufficient geopolymerization gel to fill micro-voids was found to be 20%.